(untitled) (LACCEI, 2024)
University rankings have emerged in recent years as the preferred indicator to compare somehow the quality of higher education institutions and underline the tough competition for attracting resources and students, not to mention their impact on the media. The figures from these rankings show that research has become one of the main assets of the university system. Since undergraduate instruction focuses on professional education, we reflect on whether undergraduate academic excellence should rely only on research activity or also on teaching and learning quality in terms of competency achievement and learning outcomes. Hence the latter should also be considered as a relevant feature within higher education rankings. Accreditation criteria look for quality education evidence. Surprisingly, the criteria employed by accreditation agencies for undergraduate programs lie far from the composite indexes used by ranking agencies to measure quality outcomes. In this study, we have found controversies and disagreements in the rankings. We influence and deepen what other publications support, concerning indicators that do not agree. With simple statistical calculations, we show the inconsistency in some rankings, in alignment with what other publications state. This work overviews some national and international relevant rankings for Latin American universities, analyzes their criteria, and compares them. It also gives an insight into some dimensions proper for assessing quality in undergraduate higher education institutions (HEIs). Finally, this study suggests a group of quality indicators suitable for elaborating undergraduate education rankings. We conclude that HEIs should open a debate on the appropriate dimensions and criteria to measure undergraduate instruction quality in universities. Such dimensions also include features such as the impact on human progress, transversal competences, global competencies, and commitment to sustainability.